Information seeking / providing sequence and question-answer response in doctor-elderly patient-companion consultation - Suhail, Rana Azzah (2017)
Doctor- elderly patient-companion communication is an important area to study. How doctors exchange information with their elderly chronic illness patients-companions and manage communication during consultations is largely absent from research literature in the Arab context. This is because triadic communication appears to be a neglected subject of research in the medical domain. Addressing this gap, information exchange among medical doctors, patients and their companions at three selected private clinics and a teaching hospital in Iraq are investigated. More specifically, this study examines the general structure of the elderly triadic (doctor-patient-companion) consultation. The study sought to investigate the discourse patterns and sequence structure of information exchange during triadic consultations in the selected private clinics and the teaching hospital. The theoretical framework that is used to examine the general structure of the consultations and the discourse patterns and sequence structures of information exchange is Searle’s (1968) speech acts theory illocutionary domain, Sacks, Schegloff, and Jefferson’s (1974) conversation analysis, turn-taking model, and the typology of questions that physicians use to solicit patients’ problems, and Have’s (2002) “ideal model” of general structure of the consultation phases are used to examine the consultation phases and information seeking/providing patterns during elderly triadic consultations in these selected private clinics and the teaching hospital. Data were collected using a qualitative approach by using audio recordings. All the recorded data were transcribed using Jefferson’s transcription Notation. All the thirteen (13) consultations were transcribed and analysed. The findings show that the discourse of the consultations through which the information exchange is examined at all thirteen consultations phases are found to consist of unique sequences and patterns of information exchange due to the companions’ presence during medical consultations. These consist of speaking on behalf of the patient, speaking to the patient, speaking about the patient, and speaking for the patient through asking questions, answering questions directed to the patient and volunteering information. This in turn affected the patients’ role during the consultation and the information seeking/providing sequences during medical consultations. Lastly, implications for the study indicate that the narrow focus on doctor-patient communication and a neglect of the relational function of discourse may give rise to negative perceptions among both doctors and patients. It is therefore proposed that the findings from this study be used in doctors training programmes to raise awareness of patterns of discourse behaviour during medical consultations, with a view to improving the professional experience and skills of doctors.